Planning energy interventions in buildings and tackling fuel poverty: Can two birds be fed with one scone?. (November 2022) - Abbasi, Mohammad Hosein; Abdullah, Badr; Castaño-Rosa, Raúl; Ahmad, Muhammad Waseem; Rostami, Ali; Cullen, Jeff
Abstract: Energy retrofitting and renovations are an inseparable part of decarbonisation strategies in the building sector. These measures are often tied up with several social factors that can potentially impact the wellbeing of households and the community if the end-user requirements are not carefully considered. Fuel poverty is one of these social factors that is an essential consideration for designing effective, just, and user-centred interventions, but it is often overlooked in engineering processes. Therefore, this article seeks to re-connect the notion of fuel poverty to practice by bringing it forward from the post-intervention assessments to the design and decision-making stages. To do so, a new indicator, Potential Fuel Poverty Index (PFPI), is developed to obtain the likelihood of fuel poverty that future interventions can pose to the households. The PFPI presents a more targeted analysis of fuel poverty by reflecting the socio-spatial characterisation of the households. Using the PFPI, fuel poverty can be observed as a design/decision factor at the early stages of sketching interventions, in conjunction with other economic, environmental, and technical factors. Finally, the utility of the developed method is demonstrated using a real case study in the UK, assessing the impact of heat decarbonisation through heat pumps on fuel poverty. Graphical abstract: Unlabelled Image Highlights: Social indicators of sustainability are often overlooked in designing and planning building interventions. Fuel poverty can be predicted at the early stages of building interventions. A method is proposed to give precedence to fuel poverty, bringing it forward from post-intervention to primary stages. Using the developed method, energy interventions can be adjusted to alleviate fuel poverty Implementing low-carbon energy technologies without observing fuel poverty could increase the risk of energy deprivation.